Man and environment in India through ages an interdisciplinary study of the Indian quaternary with focus on north-west - Agrawal, Dharma P. 1935- (Books & Books, 1992)
Geological history of Kashmir.
Keywords: Loess - Inde - Aspect de l'environnement - Histoire; Paléoclimatologie - Inde - Aspect de l'environnement; Paléoclimatologie - Quaternaire; Quaternaire; Stratigraphie; Geschichte; Umwelt; Geology, Stratigraphic -- Quaternary; Loess -- India -- Environmental aspects -- History; Paleobotany -- Quaternary; Paleoclimatology -- Quaternary; Paleoclimatology -- India -- Environmental aspects; Mensch; Inde - Aspect de l'environnement - Histoire; Indien; India -- Environmental conditions -- History